Classics in Israel: Where Do We Go From Here? - Amitay, Ory (Scripta Classica Israelica, 2023)
Beyond the usual talk about the crisis of the Humanities, the situation of Classical Studies in Israel is complicated also by local peculiarities of Israeli society. First and foremost among them is the bad reputation enjoyed by Greek and Roman cultures, because of their respective roles in ancient Judean history, and of the perceptions of this history in modern Israel. This short paper addresses the problem and offers three possible avenues for some improvement: (a) The use of digital means to expand the teaching of the classical languages; (b) an engagement of the Classical Studies community in the Hebrew Wikipedia; (c) an emphasis on translation into Hebrew in PhDs.